Stabilität und Flexibilität Wie und warum ändern sich Ministerien? - Bertels, Jana (Modernisierung des öffentlichen Sektors ("Gelbe Reihe"), 2018)
How and why do the formal structures of ministerial departments change? This study presents the findings of the first comprehensive formal analysis of the organisational structure of Germany's federal bureaucracy between 1980 and 2015. It describes its internal structural dynamics over time, including the frequency and distribution of its organisational units, its structural volatility and the variety of structural changes it has undergone. In addition, the study discusses key theoretical perspectives from political science and public administration debates in order to explain these structural dynamics. Its empirical analyses show that German ministerial departments have become more fragmented over time as a result of both (partisan) politics and also sectoral features. Illustrated with many examples, this study thus shows which external and internal determinants have shaped the structural dynamics of Germany's federal bureaucracy.